Odpowiedzi

2010-03-23T19:42:02+01:00
3(5a+3b)-(10a+10b)=3(5*-1/5+3*0,2)-(10*-1/5+10*0,2)= 3(-1+1,2)-(-2+5)=3*0,2-3=1,2-3=-1,8
2-10(2y-x)+2(-y+4x)=2-10(2*-0,1+1)+(0,1+4)=2-10*0,8+4,1=2-8+4=-2
-2(-3x-y)-3x(1+y)=-2(-3*2-1/4)-3*2(1+1/4)=-2*-23/4-6*5/4=23/2-15/2=8/2=4
2010-03-23T19:49:58+01:00
1) 3(5a+3b)-(10a+10b) = 15a+9b-10a+10b = 5a+19b a=-1/5, b=0,2
5*(-1/5) + 19*0,2 = -1+3,8 = 2,8

2) 2-10(2y-x)+2(-y+4x) = 2-20y+10x-2y+8x = 2-22y+18x x=-1,y=-0,1
2-22*(-0,1)+18*(-1) = 2-2,2-18 = -18,2

3) = 6x+2y-3x-3xy = 3x+2y-3xy = 3*2+2*1/4-3*2*1/4= 6+1/2-3/2 = 8
2010-03-23T19:58:34+01:00
3(5a+3b)-(10a+10b)= dla a=-1/5 b=0,2
3(5*(-1/5) + 3*0,2) - (10*(-1/5) +10*0,2)= 3(-1+0,6)-(-2+2)=-3+3,6=0,6

2-10(2y-x)+2(-y+4x)= dla x=-1 y=-0,1
2-10(2*(-0,1)-(-1))+2(-0,1+4*(-1)=2 -10(-0,2+1) - 0,2-4=2-10*0,8-4,2=2-8-4,2=-10,2

-2(-3x-y)-3x(1+y)= dla x=2 y=1/4
-2(-3*2-1/4)-3*2(1+1/4)=(6*(-4)-1/2)-6(1+1/4)=(-24-1/2)-6+1/4=-24 1/2-6+1/4=-30 1/2+1/4=-30 1/4